Decoding greenwashing: how young adults perceive and react to sustainability claims on social media - Landwehr, Kendall, author; Dahl, Jamie, advisor; Baudoin-Farah, Andrea, committee member (Colorado State University. Libraries, 2025)
As the impacts of climate change intensify globally, consumers increasingly expect companies to adopt more socially and environmentally responsible business practices. Yet, as companies are incentivized to act sustainably, many engage in greenwashing– the practice of exaggerating or falsifying their environmental claims. This study investigates how young adults aged 18-24 encounter greenwashing on social media and how such exposure shapes their attitudes and consumer behavior. An online survey was administered to assess participants' daily social media use, recognition and understanding of greenwashing, and responses to sustainability-related claims. Participants reported extensive daily social media use and frequent exposure to environmental messaging through influencer and product marketing. Participants often struggled to distinguish between misleading claims and honest sustainability efforts. Although most respondents reported they would avoid a product or brand if they suspected greenwashing, 67% had not done so in practice, revealing an attitude-behavior gap. Perceptions varied with sustainability knowledge but respondents consistently expressed interest in companies' efforts to limit post-consumer waste, lower greenhouse gas emissions, decrease energy use, and minimize upstream and downstream operational impacts. Across respondents, concern about deceptive marketing and a strong preference for brand integrity emerged. Consumers would prefer for brands to be honest about the challenges they face in making their practices more sustainable, rather than overstate their sustainability initiatives. Specifically, participants wish to see greater transparency in sourcing, manufacturing, stakeholder engagement, and labor practices. Overall, the findings emphasize a need for improved consumer education on sustainability and stronger corporate transparency, highlighting the dual role of informed consumers and responsible companies in mitigating greenwashing.
Keywords: greenwashing; sustainability claims; Social media use; young adults; consumer behavior